The utility of micro-computed tomography for the non-destructive study of eye microstructure in snails - Sumner-Rooney, L; Kenny, NJ; Ahmed, F; Williams, ST (Springer Nature, 2019)
Molluscan eyes exhibit an enormous range of morphological variation, ranging from tiny pigment-cup eyes in limpets, compound eyes in ark clams and pinhole eyes in Nautilus, through to concave mirror eyes in scallops and the large camera-type eyes of the more derived cephalopods. Here we assess the potential of non-destructive micro-computed tomography (µ-CT) for investigating the anatomy of molluscan eyes in three species of the family Solariellidae, a group of small, deep-sea gastropods. We compare our results directly with those from traditional histological methods applied to the same specimens, and show not only that eye microstructure can be visualised in sufficient detail for meaningful comparison even in very small animals, but also that μ-CT can provide additional insight into gross neuroanatomy without damaging rare and precious specimens. Data from μ-CT scans also show that neurological innervation of eyes is reduced in dark-adapted snails when compared with the innervation of cephalic tentacles, which are involved in mechanoreception and possibly chemoreception. Molecular tests also show that the use of µ-CT and phosphotungstic acid stain do not prevent successful downstream DNA extraction, PCR amplification or sequencing. The use of µ-CT methods is therefore highly recommended for the investigation of difficult-to-collect or unique specimens.